Development of easy‐to‐use reverse‐phase liquid chromatographic methods for determining PRE‐084, RC‐33 and RC‐34 in biological matrices. The first step for in vivo analysis of sigma1 receptor agonists. (8th October 2015) - Marra, Annamaria; Rossi, Daniela; Maggi, Lauretta; Corana, Federica; Mannucci, Barbara; Peviani, Marco; Curti, Daniela; Collina, Simona
Abstract: Over the years there has been a growing interest in the therapeutic potential for central nervous system pathologies of sigma receptor modulators. The widely studied PRE‐084 and our compounds RC‐33 and RC‐34 are very potent and selective sigma 1 receptor agonists that could represent promising drug candidates for Amyotrophic Lateral Sclerosis (ALS). Herein, we develop and validate robust and easy‐to‐use reverse‐phase chromatographic methods suitable for detecting and quantifying PRE‐084, RC‐33 and RC‐34 in mouse blood, brain and spinal cord. An HPLC/UV/ESI‐MS system was employed for analyzing PRE‐084 and an HPLC/UV‐PDA system for determining RC‐33 and RC‐34. Chromatographic separations were achieved on Waters Symmetry RP18 column (150 × 3.9 mm, 5 µm), eluting with water and acetonitrile (both containing 0.1% formic acid) in gradient conditions. The recovery of PRE‐084, RC‐33 and RC‐34 was >95% in all the considered matrices. Their limits of quantitation and detection were also determined. Validation proved the methods be suitable for separating tested compounds from endogenous interferences, being characterized by good sensitivity, linearity, precision and accuracy. A preliminary central nervous system distribution study showed a high distribution of RC‐33 in brain and spinal cord, with concentration values well above the determined limit of quantitation. The proposed methods will be used in future preclinical investigations. Copyright © 2015 John Wiley & Sons, Ltd.